Định lượng asen, cadimi, chì và thủy ngân trong một số thuốc y học cổ truyền - Lê, Thị Thanh Trân (2023)
The residue of heavy metals in herbal medicines is one of the causes leading to the accumulation of these elements in the users. Currently, in Vietnam, there is no regulation on the content of heavy metals in herbal medicines. This study investigated the content of As, Cd, Hg and Pb in fourteen samples which based on the combination of different herbal medicines and four kinds of herbal medicines. They were collected on Da Lat City and Ho Chi Minh City in 2020. The analytical results showed that some samples had relatively high concentration of investigated elements. The highest content (mg.kg-1) of Cd, and Pb was 1.91 ± 0.01, 2.36 ± 0.30, respectively, in TC2 sample; the highest content of As was 1.81 ± 0.09, in SM2 sample; the highest content of Hg was 1.06 ± 0.09, in TĐ2 sample. This result should be noted to improve the quality of herbal medicines and protect the health of users.